A copper nitride nanocube catalyst for highly efficient hydroboration of alkynes. Issue 7 (3rd January 2023) - Xu, Hang; Yamaguchi, Sho; Mitsudome, Takato; Mizugaki, Tomoo
Abstract : Copper nitride nanocubes were employed as efficient heterogeneous catalysts for the hydroboration of alkynes under additive-free and mild reaction conditions. Abstract : The hydroboration of alkynes with bis(pinacolato)diboron is a useful method for the synthesis of vinyl boronate esters, which are essential intermediates in organic syntheses. Copper catalysts have been used extensively in these reactions. However, previously reported Cu-catalyst systems inevitably require additives and elevated temperatures. Herein, we report, for the first time, a simple and efficient hydroboration of alkynes under additive-free and mild reaction conditions ( i.e., at a temperature of 30 °C) using a copper nitride nanocube (Cu3 N NC) catalyst. A wide range of alkynes can be transformed into their corresponding boronate esters. Cu3 N NCs are also applicable in the hydroboration of alkynes with tetrahydroxydiboron to synthesize vinyl boronic acids. Moreover, the Cu3 N NCs were easily separated by simple filtration and could be reused several times without any loss of their original activity. Hence, these highly active and reusable Cu3 N NC catalysts offer an environmentally friendly route for the efficient production of vinyl boronates.